Microwave-assisted synthesis of BSA-stabilised gold nanoclusters for the sensitive and selective detection of lead(ii) and melamine in aqueous solution. Issue 82 (19th August 2016) - Lee, Che-Yu; Hsu, Nai-Yueh; Wu, Mei-Yao; Lin, Yang-Wei
Abstract : MW-assisted synthesis of fluorescent BSA-AuNCs for the turn-off sensing of Pb(ii ) and turn-on sensing of melamine. Abstract : In this study, a sensitive and selective fluorescence assay using the microwave-assisted synthesis of bovine serum albumin-stabilised gold nanoclusters (MW_BSA-AuNCs) was proposed for the determination of lead(ii ) and melamine in aqueous solution. The fluorescence of the MW_BSA-AuNCs was quenched through a Pb 2+ -mediated interparticle aggregation mechanism, and thus the change in fluorescence at 660 nm was dependent on the Pb 2+ ion concentration. In addition, the fluorescence of the MW_BSA-AuNCs was also quenched on the basis of the high-affinity metallophilic Hg 2+ –Au + interaction, whereas the fluorescence of the MW_BSA-AuNCs was restored when melamine was added and coordinated with Hg 2+ . Under optimal conditions, the limits of detection for Pb 2+ ions and melamine at a signal-to-noise ratio of 3 were 4.8 nM and 2.94 μM, respectively. Our present approach is simpler and more cost-effective than the existing techniques for the detection of Pb 2+ ions in seawater and aqueous urine samples and of melamine in milk samples.